Impact of FADS gene variation and dietary fatty acid exposure on biochemical and anthropomorphic phenotypes in a Hispanic/Latino cohort - Sergeant, Susan; Keith, Brian A.; Seeds, Michael C.; Legins, Jimaree A.; Young, Caroline B.; Vitolins, Mara Z.; Chilton, Floyd H. (Frontiers in Nutrition, 2023)
Polyunsaturated fatty acids (PUFA) and highly unsaturated fatty acid (HUFA) synthetic products and their signaling metabolites play vital roles in immunity, inflammation, and brain development/function. Frequency differences of variants within the fatty acid desaturase (FADS) gene cluster affect levels of HUFAs, their biologically active products, and numerous physiological phenotypes. Fundamental questions remain regarding the impact of this genetic variation on the health of Hispanic/Latino populations. Data and biospecimens (plasma, erythrocytes [RBC], buffy coat-derived DNA) from 135 participants (83.7% female) were used to assess the relationship(s) between dietary PUFA levels, a FADS haplotype tagging SNP, rs174537, and the capacity of Hispanic/Latino populations to generate HUFAs in plasma and RBC as well as its potential impact on anthropomorphic phenotypes. The dietary habits of the cohort showed that participant diets contained a high ratio (9.3±0.2, mean±sem) of linoleic acid (n-6) to alpha-linolenic acid (n-3) and also contained extremely low levels of n-3 HUFAs (eicosapentaenoic acid, EPA and docosahexaenoic acid, DHA), both features of the Modern Western Diet. The frequency of the TT rs174537 genotype was highly enriched (53% of subjects) in this Hispanic/Latino cohort (compared to African and European Americans) and was strongly associated with lower circulating HUFA levels. For example, plasma levels of arachidonic acid (ARA: 20:4, n-6) and EPA (20:5, n-3) were 37% and 23%, respectively, lower in the TT versus the GG genotype. HUFA biosynthetic efficiency, as determined by metabolic product to precursor ratios, was highly dependent (p<0.0001) on the rs174537 genotype (GG>GT>TT) for both circulating n-6 and n-3 HUFAs. In contrast, the RBC Omega-3 Index (EPA+DHA) was extremely low (2.89±1.65, mean±sd) in this population and independent of rs174537 genotype. Importantly, the rs174537 genotype was also related to female height with TT genotype participants being 4.5 cm shorter (p=0.0001) than the GG+GT participants. Taken together, this study illustrates that dietary PUFA+HUFA x FADS gene- interactions place a large proportion (>50%) of Hispanic/Latino populations at high risk of a deficiency in both circulating and cellular levels of n-3 HUFAs.